300. Trends in electrocardiographic and cardiovascular manifestations of patients hospitalized with COVID-19. (15th December 2022) - Ngiam, Jinghao Nicholas; Goh, Wilson; Sim, Meng Ying; Chhabra, Srishti; Liong, Tze Sian; Chew, Nicholas W S; Chai, Ping; Yeo, Tiong Cheng; Cross, Gail Brenda; Tambyah, Paul Anantharajah; Sia, Ching Hui
Abstract: Background: Early in the coronavirus disease 2019 (COVID-19) pandemic, a low incidence of cardiovascular complications was reported amongst hospitalised patients with COVID-19 in Singapore. Little was known about the trend of cardiovascular complications as the pandemic progressed. As such, we sought to examine the evolving trends in electrocardiographic and cardiovascular manifestations in patients hospitalised for COVID-19 infection. Methods: We examined the first 1781 consecutive hospitalised patients with polymerase chain reaction (PCR) confirmed COVID-19 in a tertiary academic centre. We divided the population based on those who had an abnormal electrocardiogram (ECG) and those who had a normal ECG, comparing the baseline characteristics and outcomes between the 2 groups. Cardiovascular complications such as acute myocardial infarction, stroke, pulmonary embolism, myocarditis and mortality were also examined over time. Results: Of the 261 (14.7%) patients presenting with abnormal ECG, they were more likely to be symptomatic with complaints of breathlessness, palpitations and chest pain. Sinus tachycardia was the most common arrhythmia. Troponin I levels (41.6±264.3 vs 97.0±482.9, p=0.047) and C-reactive protein levels (20.1±50.7 vs 13.9±24.1 µmol/L, p=0.003) were significantly higher amongst those with abnormal ECGs at presentation, with a higher prevalence of myocarditis (1.9% vs 0.5%, p=0.021), pulmonary embolism (1.9% vs 0.3%, p=0.009) and acute myocardial infarction (1.1% vs 0.1%, p=0.025). Over time, there was a trend towards a higher proportion of hospitalised patients with cardiovascular complications. Baseline characteristics of hospitalised patients with COVID-19, with or without abnormal ECG at presentation Changes in percentage of hospitalised patients with COVID-19, experiencing cardiovascular events (acute myocardial infarction, stroke, myocarditis, pulmonary embolism and death) over time Conclusion: A baseline ECG at presentation is a simple test that provides valuable information on potential cardiovascular complications in the context of COVID-19. Although the prevalence of abnormal ECGs is relatively low, it appears to be increasing over time amongst hospitalised patients with COVID-19. Disclosures: All Authors : No reported disclosures.